THE EFFECT OF INTELLECTUAL CAPITAL ON MARKET VALUE IN BANKING SECTORS LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE 2020-2024 PERIOD - Yella Deswita; Dina Patrisia (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to analyze the influence of intellectual capital on market value in banking sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. Intellectual capital is measured using the Value Added Intellectual Coefficient (VAIC) which consists of the components Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA). The analysis method used is multiple regression by considering the control variables of company size (Size) and leverage. The results of the study show that VAIC has a significant positive influence on the company's market value. This indicates that effective intellectual capital management, through human resource development, innovation, and structural efficiency, can increase stakeholder trust and drive increased market value. This study emphasizes the importance of intellectual capital management as a strategy to strengthen the competitiveness and financial performance of banking companies in the knowledge-based economy era.